2021
DOI: 10.1186/s12974-021-02271-3
|View full text |Cite
|
Sign up to set email alerts
|

HSF1 is involved in suppressing A1 phenotype conversion of astrocytes following spinal cord injury in rats

Abstract: Background Two activation states of reactive astrocytes termed A1 and A2 subtypes emerge at the lesion sites following spinal cord injury (SCI). A1 astrocytes are known to be neurotoxic that participate in neuropathogenesis, whereas A2 astrocytes have been assigned the neuroprotective activity. Heat shock transcription factor 1 (HSF1) plays roles in protecting cells from stress-induced apoptosis and in controlling inflammatory activation. It is unknown whether HSF1 is involved in suppressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Epidermal growth factor-containing hydrogels can reportedly alter astrocyte behavior, i.e., they downregulate the expression of deleterious neurotoxicity-related genes ( Fbln5 and Rt1-S3 ) while upregulating that of potentially beneficial neuroprotective phenotype-associated genes ( Clcf1 , Tgm1 , and Ptgs2 ), thereby indirectly enhancing neuroprotection and neuroplasticity (Chan et al, 2019 ). RTMS, HSF1, and physical exercise also lead to the conversion of the neurotoxic phenotype into the neuroprotective phenotype, which promotes functional recovery after injury (Zong et al, 2020 ; Jiang et al, 2021 ; Li L. et al, 2021 ). Mitochondria may also play a role in A1 polarization.…”
Section: Strategies For Astrocyte-targeted Therapymentioning
confidence: 99%
“…Epidermal growth factor-containing hydrogels can reportedly alter astrocyte behavior, i.e., they downregulate the expression of deleterious neurotoxicity-related genes ( Fbln5 and Rt1-S3 ) while upregulating that of potentially beneficial neuroprotective phenotype-associated genes ( Clcf1 , Tgm1 , and Ptgs2 ), thereby indirectly enhancing neuroprotection and neuroplasticity (Chan et al, 2019 ). RTMS, HSF1, and physical exercise also lead to the conversion of the neurotoxic phenotype into the neuroprotective phenotype, which promotes functional recovery after injury (Zong et al, 2020 ; Jiang et al, 2021 ; Li L. et al, 2021 ). Mitochondria may also play a role in A1 polarization.…”
Section: Strategies For Astrocyte-targeted Therapymentioning
confidence: 99%
“…In the same year, in another study, Li et al. demonstrated that heat shock transcription factor 1 plays a key role in suppressing the excessive increase in neurotoxic A1 astrocytes ( 41 ). Wang et al.…”
Section: How Are the Functions Of Immune Cells And Immune Factors Orc...mentioning
confidence: 97%
“…In 2021, Zhang et al found that miR-21a-5p can aggravate the inflammatory response after traumatic SCI by increasing A1 polarization via the inhibition of the CNTF/ STAT3/Nkrf signaling pathway (40). In the same year, in another study, Li et al demonstrated that heat shock transcription factor 1 plays a key role in suppressing the excessive increase in neurotoxic A1 astrocytes (41). Wang et al showed that the transformation of A1/A2 reactive astrocytes may be associated with functional recovery after SCI (42).…”
Section: The Dual Roles Of Astrocytes In Spinal Cord Injury Pathophys...mentioning
confidence: 99%
“…HSF1 regulates NF-κB activity by inhibiting the nuclear binding activity of NF-κB or decreasing the degradation of IκB protein. It binds to promoters to inhibit TNF-α and IL-1β expression, ultimately down-regulating the transformation of A1 astrocytes . Promoting the conversion of the A1 subtype to the A2 subtype can effectively suppress inflammation.…”
Section: Glial Cells In the Central Nervous System And Inflammatory Painmentioning
confidence: 99%
“…54 Astrocytes have been shown to have two subtypes, A1 and A2. A1 astrocytes are induced by cytokines such as IL-1α and 58 Promoting the conversion of the A1 subtype to the A2 subtype can effectively suppress inflammation. Melatonin reduces the number of A1 astrocytes and increases the number of A2 astrocytes through the melatonin receptor 1A (MT1)/JAK2/STAT3 pathway and regulates the transformation of astrocytes from A1 subtype to A2 subtype.…”
Section: Glial Cells In the Central Nervous Systemmentioning
confidence: 99%